How are India’s districts doing on maternal, infant and young child nutrition? Insights from the national family health survey-4 - Menon, Purnima; Mani, Sneha; Nguyen, Phuong Hong (International Food Policy Research Institute, 2017)
A set of global nutrition targets for maternal, infant and young child nutrition to be achieved by 2025, were endorsed by the World Health Assembly (WHA)in 2012. These targets provide goals against which progress towards ending malnutrition in all its forms can be measured and also contribute to the Sustainable Development Goals (SDGs). This Data Note describes the current levels of a set of these key nutrition out comes at the district-level in India, summarizing data from the recently released district factsheets of the National Family Health Survey.